2023
DOI: 10.1039/d3cy00597f
|View full text |Cite
|
Sign up to set email alerts
|

Improved NH3-SCR activity by the cooperation of FeVO4 and CeO2 nanosheet catalysts: structure and mechanism

Abstract: A series of FeVO4/CeO2 nanosheet catalysts featuring various mass percentages (x%) of FeVO4 (denoted x%FeV/CeO2-S) were synthesized and employed in selective catalytic reduction of NOx with NH3. Among them, 10%FeV/CeO2-S...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The two-dimensional characteristics show great potential for achieving high activity of catalysts due to structural advantages. [33][34][35][36] Furthermore, a homogeneous dispersion of La, Ni, and O elements is demonstrated by the energy dispersive X-ray (EDX) elemental mapping images of La-Ni(OH) 2 /NF (Fig. 1e).…”
Section: Resultsmentioning
confidence: 99%
“…The two-dimensional characteristics show great potential for achieving high activity of catalysts due to structural advantages. [33][34][35][36] Furthermore, a homogeneous dispersion of La, Ni, and O elements is demonstrated by the energy dispersive X-ray (EDX) elemental mapping images of La-Ni(OH) 2 /NF (Fig. 1e).…”
Section: Resultsmentioning
confidence: 99%
“…For the method of characterization, refer to refs , , and the detailed descriptions are provided in the Supporting Information.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…For all catalysts, the V 2p 3/2 peaks were fitted into V 5+ (516.8−516.9 eV) and V 4+ (515.7−515.9 eV) peaks. 24,34,38 The atom ratio of V 5+ /V 4+ in D-0.5KN, D-0.5KCl, and D-0.5KS catalysts decreased to 0.64, 0.66, and 0.76, respectively, in comparison to the fresh catalyst (1.11). This indicated that both K 2 O and KCl had similar effects on the chemical state of V species on the surface of the catalysts, and their influences were more severe than that of K 2 SO 4 .…”
Section: Xps Studymentioning
confidence: 99%
“…5,11,12 Therefore, modification of iron oxide catalysts has received extensive attention, and Fe-based catalysts for NO x reduction have been prepared by doping with other metal species and sulfate-modification to regulate the acidity and reducibility. Examples include FeNbO x , 9 Fe/Zr–W, 13,14 Fe–W, 15 Fe–Ce, 16 Fe–Ce–V, 17,18 Fe–Mn–Ce, 19,20 Fe–SO 4 /TiO 2 , 21 FeZrCeTiO x , 22 Mn–Fe–Ce/ACN, 23 MnFeW/Ti, 24 and Fe–Mn–Mo/TiO 2 . 25…”
Section: Introductionmentioning
confidence: 99%